US foreign policy and transatlantic security relations after the elections - Peter Rudolf (Stiftung Wissenschaft und Politik (SWP), 2008)
The election campaign rhetoric on foreign policy issues is no direct indicator of the strategic priorities a new US President will set later - nor is it indicative of the actual policies which will be adopted. It does, however, reflect the ideological framework in which he and his circles of advisors operate. Leaving aside the numerous tactical controversies, the current foreign policy debate in the US displays a rather broad consensus that the country should continue to play a leadership role in international relations. Neither too much concern about a re-ideologisation of foreign policy under John McCain nor an all too hopeful anticipation of a multilateral foreign policy under Barack Obama is appropriate. Considerable continuity in US foreign policy rather than a fundamental shift is the more likely outcome of the upcoming change in the White House
Keywords: 320